2013
DOI: 10.3127/ajis.v18i1.809
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and motivations affecting Information Systems usage by Hajj–Umrah religious tourism operators in Saudi Arabia

Abstract: Hajj & Umrah religious tourism accounts for seven million visitors each year in Saudi Arabia. The government has recently taken initiatives to promote the use of Information Systems (IS) in the religious tourism industry, encouraging firms to adopt IS innovations like e-commerce and enforcing the use of the Makha'a information system in Umrah for external pilgrims and the Yosr information system in Hajj for internal pilgrims. This study outlines the motivations and challenges that affect the utilisation of var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 19 publications
1
6
0
Order By: Relevance
“…While the internal factors have three dimensions that are all significant, namely corporate culture, corporate structure, and corporate resources. These results are in line with (Brdesee, Corbitt, & Pittayachawan, 2013;Hidayat et al, 2015;Morioka & de Carvalho, 2016;Porter, 2008;Rundh, 2009) which states that the external and the internal factors are the main factors in a business environment. The following explanation is given on the research findings:…”
Section: Figure 2 Pls Algorithmsupporting
confidence: 86%
“…While the internal factors have three dimensions that are all significant, namely corporate culture, corporate structure, and corporate resources. These results are in line with (Brdesee, Corbitt, & Pittayachawan, 2013;Hidayat et al, 2015;Morioka & de Carvalho, 2016;Porter, 2008;Rundh, 2009) which states that the external and the internal factors are the main factors in a business environment. The following explanation is given on the research findings:…”
Section: Figure 2 Pls Algorithmsupporting
confidence: 86%
“…An interview guide was used to cover a broad range of topics related to Umrah DIY. The interview guide consisted of three main sections, where open-ended interview questions were used, except for the section on the sociodemographic information (Brdesee et al, 2013). In the first section, respondents were asked to share their socio-demographic characteristics, such as gender, age, educational level, occupation, and household income.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, there are also a growing interest for the study of the effect of technology and artificial intelligence for enhancing the Umrah experience and satisfaction. For example, Virtual Reality (VR) Based Interactive (Kabir et al, 2021), User Interface on Virtual Umrah (Isa et al, 2017), information system (Brdesee et al, 2013), information and communication technology (ICT) and apps usability (Hassan et al,2022) are regarded to have a positive effect on boosting the positive Jemaah or pilgrims experience. Thus, it showed that information and communication technology (ICT) has a significant impact on religious tourism, with implications for the specifics of religious sites and the practises, traditions, and rituals connected to them (Hassan et al, 2022) Different authors defined Umrah in different ways, which are shown in Table 1.…”
Section: Literature Reviewmentioning
confidence: 99%